Reduction of Metal Artifact with Dual-Energy CT: Virtual Monospectral Imaging with Fast Kilovoltage Switching and Metal Artifact Reduction Software - Pessis, Eric; Sverzut, Jean-Michel; Campagna, Raphaël; Guerini, Henri; Feydy, Antoine; Drapé, Jean-Luc (Seminars in Musculoskeletal Radiology, 2015)
Imaging of patients with metal implants is a common activity for radiologists, and overcoming metal artifacts during computed tomography (CT) is still a challenge. Virtual monochromatic spectral (VMS) imaging with dual-energy CT has been reported to reduce beam-hardening metal artifact effectively. Dual-energy CT allows the synthesis of VMS images. Monochromatic images depict how the imaged object would look if the X-ray source produced X-ray photons at only a single-energy level. For this reason, VMS imaging improve image quality by reducing beam-hardening artifacts. Additional metal artifact reduction postprocessing such as metal artifact reduction software can be applied to improve the visualization of the bone–prosthesis interface, periprosthetic areas, and soft tissue near and far from the metal implant. This article summarizes how virtual monochromatic images are synthesized from dual-energy CT, and it describes and illustrates our clinical experience with a single-source dual-energy scanner with fast kilovoltage switching to reduce beam hardening in patients with metal implants.
Keywords: artifacts; metals; prostheses and implants; dual-energy CT; metal artifact reduction software